Diana Thater. Keep The Faith. A Survey Exhibition. - Abegg, Georg; Durham, April; Engelbach, Barbara; Herzogenrath, Wulf; Thater, Diana; Exhibition. Diana Thater. Keep The Faith. A Survey Exhibition. (1). Exhibition. Diana Thater. Keep The Faith. A Survey Exhibition. (2). Kunsthalle Bremen. Museum für Gegenwartskunst Siegen. 2004-03-19. 2004-03-21. 2004-06-20. 2004-06-20 (Bremen Köln Siegen : Kunsthalle Bremen Museum für Gegenwartskunst Siegen Salon Verlag & Edition Köln, 2004)
To inspire the installation of this survey exhibition, I started with these two pieces of text, one for each of the museums involved. Here are two variations on the same theme : the interconnectedness of history (the past) and beauty (the present). That art is dependent on depth, meaning and belief is proposed in every body of work included in this exhibition. The final two lines of the texts are the same : Screw The Market. Keep The Faith. These perhaps are self-explanatory... Diana Thater Diana Thater began exhibiting in 1990 and has made some of the most important innovations in video installation since its recognition as an art form. While most artists working in video rely on projected narrative, Thater has made her own extensive investigations into abstraction, editing, moving images in space and, into installation technique. To do this she uses the two key materials of installation : time and space. The spatio-temperal dimension of her complex art are visible in the works in this exhibition, from the earliest piece chosen, Abyss of Light (1993) to the most recent Orange Room (Wallflowers) (2001).
bibliog. p. 98-99
biog., ind. tent. p. 96, gr. tent., exhitions curated by the artist, performances p.97-98
Duits
Engels
boek
Keywords: Thater, Diana